Eliminating Mental Health Stigma and Building Resilience: A Psychological Approach in Muslim Communities - Syed Zainal Ariff, Sharifah Nadirah (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2025)
Stigma toward mental illness is a major barrier to individuals experiencingpsychological distress within Muslim communities. Cultural stigma, often misinterpreted asreligious doctrine, has become deeply rooted and influences community perceptions,contributing to low awareness and limited understanding of the importance of mental health. Therefore, this study aims to identify common forms of stigma and explore Islamic value-based peer support models for strengthening resilience. The method used was Systematic Literature Review (SLR) guided by the Preferred Reporting Items for Systematic Reviews andMeta-Analyses (PRISMA) 2020 framework. A comprehensive literature search wasconducted through Google Scholar and PubMed. The inclusion criteria were scholarly articlespublished between 2015 and 2025, leading to 16 studies meeting the selection requirements.The results showed that familial stigma, community attitudes, and misattributed spiritualbeliefs are the main obstacles to seeking professional help. However, integratingpsychological approaches with faith-based frameworks improved awareness, reducedstigma, and enhanced individual resilience. This study is expected to inform the developmentof more effective and culturally sensitive peer support programs in Muslim communities.